The Politics of Social Protection in Eastern and Southern Africa - Hickey, Sam; Lavers, Tom; Niño-Zarazúa, Miguel; Seekings, Jeremy (Oxford University Press, 2019)
The notion that social protection should be a key strategy for reducing poverty in developing countries has now been mainstreamed within international development policy and practice. Promoted as an integral dimension of the post-Washington Consensus that emerged around the turn of the new millennium, all major international development agencies and bilateral donors now include a strong focus on social protection in their advocacy and programmatic interventions, and a commitment to providing social protection was recently enshrined within the Sustainable Development Goals. The rhetoric around social protection, particularly when delivered in the form of cash transfers, has sometimes reached hyperbolic proportions, with advocates seeing it as a silver bullet that can tackle multi-dimensional problems of poverty, vulnerability, and inequality and a southern-led success story that challenges the unequal power relations inherent within international aid. This book examines how the operation of power and politics at multiple levels of governance shapes the extent to which political elites are committed to social protection, the form this commitment takes, and the implications this has not only for the future shape of welfare regimes but also for state-citizen relations on the continent. With a particular focus on cash transfers, the chapters set out how the politics of promoting social protection has played out in countries from all regions of sub-Saharan Africa. The power relations we examine include those that operate within and amongst global development agencies, between global actors and political and bureaucratic elites, and between and amongst political and bureaucratic elites within Africa.